Scatter simulation and correction in computed tomography: A reconstruction-integrated approach modelling the forward projection. (March 2017) - Dremel, Kilian; Fuchs, Theobald
Abstract: Scattered photons lower the quality of the reconstructed images in computed tomography. Additionally to scattering in the scintillator material that lowers the resolution, object-scattered photons cause artefacts due to non-linear absorption and are difficult to simulate. In the context of model-based reconstruction we developed a fast approximation for scattered radiation that is integrated in the forward projection of an iterative polychromatic reconstruction method. We develop the modelling of scattered intensities in an iterative maximum-likelihood reconstruction method, demonstrate a comparison with Monte-Carlo simulated scatter-data and show the result of reconstructed data within the field of industrial non-destructive testing. Abstract : Highlights: Deterministic simulation of X-ray scattered photons in computed tomography (CT). Integration of object scattering in model-based reconstruction of CT data. Comparison between Monte-Carlo simulated and reconstruction-integrated simulation data. Application of the proposed method to industrial data.